Low birthweight increases risk for cardiovascular disease hospitalisations in a remote Indigenous Australian community - a prospective cohort study - Luke Arnold; Wendy Hoy; Zhiqiang Wang (Elsevier, 2016)
Abstract Objectives: To investigate the association between low birthweight (LBW; <2,500 grams) and cardiovascular disease (CVD) hospitalisations in adult life in a remote Indigenous Australian community. Methods: This was a prospective cohort of 852 participants with recorded birthweight using community‐wide health screening examinations conducted between 1992 and 1999 and hospitalisation records up to 2012. Cox proportional hazard models assessed the association between LBW and hypertension, major CVD (heart failure, myocardial infarction and stroke) and any CVD hospitalisations. Results: There were 236 participants (28%) who had a low birthweight. The LBW group had a higher risk of developing any CVD (HR = 1.43, 95%CI 1.01-2.03), major CVD (HR = 1.51, 95%CI 0.93-2.47) and hypertension (HR = 1.83, 95%CI 1.09-2.96) than the normal birthweight (NBW) group (≥2,500 g). Women with LBW had more than 2.6 times the risk of a hospitalisation associated with hypertension compared to their NBW counterparts (HR = 2.61, 95%CI 1.38-4.93), but this relationship was not seen in men. Conclusions and implications: LBW increased the risk of cardiovascular disease hospitalisations in adult life in this group. Further CVD prevention initiatives should continue to include LBW as a key predictor of CVD in this community. The mechanisms of gender influence on the hypertension relationship are unknown and require further investigation in indigenous populations worldwide.